STUDI TENTANG APARATUR SIPIL NEGARADI LINGKUNGAN KANTOR CAMAT TENGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA - Andi Setiawan (ADMINISTRASI PUBLIK, 2017)
In the sense of civil state apparatus is inseparable from the Law of the Republic of Indonesia No. 5 of 2014 on State Civil Apparatus. The law of both civil servants (PNS) and government officials with work agreements (PPPK) is given the opportunity to occupy a position in a government agency. The purpose of this study is to know how the views of work and performance civil state apparatus and its influence in the view of employees. To achieve these objectives, the research method used is quantitative and data analysis techniques used are descriptive. The unit of analysis is individual and data collection is done by filling out questionnaires, observation, and interviews as well as documentation to provide information about job views and Employee Performance. Source of data used comes from primary data and secondary data. From this research, it can be concluded that the work performance and performance of civil servants of State apparatus in Tenggarong sub-district are generally considered to be good, based on the final value of the work target and the performance of each employee by accumulating the value of Employee Work Objectives (SKP) and work behavior So that it can be summed up at a